The Effectiveness of Google Classroom in Learning - Nurul . Khoiriyah; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2022)
Since the present of Corona virus, all aspects of human live are changed. This also happened in education field. Because of this pandemic, students and teachers have to do online learning. Online learning by utilizing technology demands innovation and creativity in learning activities. One way that can be used to do the learning process online is using Google Classroom digital media. The aim of this study is to evaluate Students’ perceptions on the effectiveness of Google Classroom as a Digital tool in Teaching and Learning. The study was conducted through a descriptive qualitative with Survey Research Design to investigate the Students’ Perceptions. Data analysis was conducted using Descriptive Statistics. The results of the study indicated that Google Classroom is effective in improving Students access and attentiveness towards learning, knowledge and skills gained through Google Classroom. Make Students to be active learners, as a Digital Tool, it provides meaningful feedback to both Students and Teachers.